Optimizing the Halal Food Industry Cluster as a Pillar of the Indonesian Economy - Lutfiyah Rahma Novelika; Annisaa Nurul Ramadhani Novelika (Universitas Negeri Surabaya, 2026)
Indonesia has substantial potential to become a global hub for the halal food industry due to its large Muslim population and increasing demand for halal products in both domestic and international markets. However, the potential of halal food industry clusters, particularly among micro, small, and medium enterprises (MSMEs), has not yet been fully optimized. This study aims to examine strategies for optimizing halal food industry clusters as a pillar of the Indonesian economy. A qualitative approach was employed using primary and secondary data collected through literature reviews and relevant online sources. The data were analyzed descriptively to identify key factors supporting halal industry development. The findings indicate that strengthening halal certification systems, expanding halal industrial zones, increasing halal literacy among MSMEs, enhancing government policy coordination, promoting domestic halal products, and developing international business networks are essential strategies for improving the competitiveness of halal food clusters. Community participation and collaboration among government institutions, industry actors, and consumers also play a crucial role in supporting sustainable halal industry development. The study concludes that an integrated cluster-based approach can strengthen MSME competitiveness, expand market access, and support Indonesia’s ambition to become a leading global halal industry hub while promoting long-term economic sustainability.